Resultados de un programa de rehabilitación neurocognitiva en pacientes con secuelas de trauma craneoencefálico (2016)
Introduction: Neurocognitive rehabilitation have been affected by careless monitoring provided after hospitalization. Following a multidisciplinary intervention during rehab, some improvement is expected with regards complications affecting a patient's cognitive, emotional, behavioral, social and vocational circumstances. Objective: To assess the effect of a rehabilitation program neurocognitive processes attention, memory and executive function in patients with traumatic brain injury (TBI). Methods: This would be measure through a neurocognitive rehabilitation program demonstrated with results based on the memory function and attention span. This neurocognitive rehabilitation program is design to highlight the cognitive process that act as an object of intervention: (guidance/orientation, attention, memory, executive functions, languages, behavioral manners and affective) and it was developed through 60 individual sessions and 10 collective sessions over 5 months. Results: In the results provided by the NEUROPSI test, patients from the study group showed a better performance, and significant differences were observed in memory process, attention span (p = 0,0018) and executive function (p = 0,028). Conclusions: Given the preliminary findings from the study, we suggest that changes in cognition during a patient's attention span could be linked to the implementation of this neurocognitive program.